Lady X : a novel - Fader, Molly (Ballantine Books, 2026)
"Los Angeles, 2024. After learning that her A-list actor husband sent explicit photos to multiple girls on social media, Margot Cooper runs away from the world -- and the paparazzi -- by fleeing to her childhood home with her teenage daughter in tow. But home isn't the sanctuary Margot was hoping for. In a cardboard box in the corner of the attic, she finds damning evidence of an infamous urban legend, the mysterious vigilante "Lady X" -- including a blurry newspaper photo of a woman who looks an awful lot like Margot's mother. New York City, 1977. In the midst of an infamous summer, Ginger Daughtry and her two beloved roommates are able to shield one another from the chaos -- until one of them is assaulted. Astounded by the lack of response from police, the young women decide to engage in some light payback, signing their handiwork as "Lady X." Soon copycats appear, and a movement inspired by acts of vandalism against terrible men spirals out of control, with criminals running amok under the guise of the enigmatic Lady X. When a body is found fallen -- or pushed -- from five stories high, the hunt reaches a boiling point." --